EVALUASI SISTEM INFORMASI AKUNTANSI PADA PENJUALAN KREDIT TERHADAP PENGENDALIAN INTERNAL - Shintya Permata Sari; Isnaini Anniswati Rosyida (Fakultas Ekonomi, 2023)
This study aims to evaluate whether the components of the credit sales accounting information system at PT. Tunas Makmur Jaya Abadi has been running well or not, especially in terms of internal control whether it is in accordance with standards or vice versa. This research is a descriptive qualitative research, namely research that focuses on collecting data through interviews that are collected and then processed into information and also makes the data described in a flowchart so that an evaluation of the Credit Sales Accounting Information System on Internal Control and Effectiveness of the Implementation of Information Systems can be carried out. Accounting Against Credit Sales. Based on the results of the study, it was concluded that the credit sales accounting system at PT. Tunas Makmur Jaya Abadi has been running well or has been effective and the existing internal control system in the company PT. Tunas Makmur Jaya Abadi has been running well by separating functions and responsibilities strictly in each unit of the organizational structure.